Implementasi Inklusi Keuangan dan Sistem Informasi Akuntansi untuk Optimalisasi Kinerja Keuangan di Kabupaten Sleman - Syanindita Perwitasari; Baniady Gennody Pronosokodewo (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to examine the effect of financial inclusion, accounting information systems, and e-commerce on the financial performance of Micro, Small, and Medium Enterprises (MSMEs). MSMEs play a crucial role in supporting regional economic growth, thus enhancing financial performance is a crucial aspect. The study sample comprised 84 MSME owners in Sleman Regency, drawn using the snowball sampling technique. Data collection was conducted through online questionnaires using a Google Form link to facilitate respondents' completion and to broaden the reach of respondents. The data were analyzed using multiple linear regression with SPSS software to determine the extent of the interplay between the variables studied. The results indicate that financial inclusion has a positive effect on MSME financial performance. This indicates that the easier access for MSMEs to formal financial services, the better their financial performance. Similarly, accounting information systems have also been shown to have a positive effect, where the implementation of a good accounting system can improve the quality of transaction recording and financial decision-making. Conversely, e-commerce has not been shown to have a significant effect on MSME financial performance. This finding indicates that the use of e-commerce by MSMEs in Sleman is not optimal in supporting improved financial performance.